Lithium-rich manganese-based positive electrode active material and preparation method and application thereof

By adopting a lithium-rich manganese-based positive electrode active material with a multi-layer clad structure, the problems of storage capacity loss and increased storage impedance of lithium-rich manganese-based materials in the field of lithium-ion battery positive electrode materials are solved, and high capacity, high stability and excellent cycling performance are achieved.

CN119812266AActive Publication Date: 2025-04-11NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD

Patent Information

Application Number
CN202411996575.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

Lithium-rich manganese-based materials face problems such as loss of storage capacity and increased storage impedance in the field of lithium-ion battery positive electrode materials, which limits their commercial applications.

Method used

The lithium-rich manganese-based positive electrode active material adopting a multi-layer cladding structure includes a lithium-rich manganese-based core, a first cladding layer and a second cladding layer. The first cladding layer consists of X-doped nanolayer lithium cobalt oxide, and the second cladding layer comprises a fast ion conductor and/or spinel-like cobalt lithium compound.

Benefits of technology

By optimizing the core composition and designing the cladding structure, the storage capacity, cycle stability and rate performance of the material are significantly improved, and the conductivity and interface stability of lithium ions are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812266A_ABST
    Figure CN119812266A_ABST
Patent Text Reader

Abstract

The invention provides a lithium-rich manganese-based positive electrode active material and a preparation method and application thereof. The lithium-rich manganese-based positive electrode active material comprises a lithium-rich manganese-based core, a first coating layer and a second coating layer, the chemical formula of the lithium-rich manganese-based core is Li < 1 + x > Ni Mn M < c > O < 2 + x >; 0.25 < = x < = 0.4, a + b + c = 1, 0.33 < = a < = 0.35, 0.63 < = b < = 0.65, and 0 < = c < = 0.02; m is selected from at least one of W, Ta, Nb, Ti, Sb, Al, Mg, Zr, Sr and Mo; the first coating layer is X-doped nano layered lithium cobalt oxide, and X is selected from at least two of Al, La, Nb, Sr, Ti, Mn, Mo, Ta, W, K, B and F; and the second coating layer comprises a fast ion conductor and / or a spinel-like phase cobalt lithium compound. The positive electrode active material provided by the invention has excellent storage capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a lithium-rich manganese-based positive electrode active material, in particular to a lithium-rich manganese-based positive electrode active material and a preparation method and application thereof, belonging to the technical field of secondary batteries. Background Art

[0002] Lithium-rich manganese-based materials are a new type of lithium-ion battery cathode material. Due to their unique chemical structure, lithium-rich manganese-based materials can provide higher energy density than traditional lithium-ion battery cathode materials. In addition, manganese resources are abundant and inexpensive. Compared with other transition metals such as cobalt, the use of manganese can significantly reduce material costs. At the same time, manganese is relatively environmentally friendly, reducing the use of heavy metals that are harmful to the environment. Therefore, manganese-rich materials are considered to be the next generation of high-performance and low-cost lithium battery cathode materials.

[0003] However, lithium-rich manganese-based materials still face some problems in practical applications, such as storage capacity loss and storage impedance increase far higher than that of ternary materials, which seriously limits their commercial application.

[0004] Therefore, how to improve the storage capacity of lithium-rich manganese-based materials and thus accelerate their promotion in the field of lithium-ion battery positive electrode materials has become a technical problem that needs to be urgently solved by technicians in this field. Summary of the invention

[0005] The present invention provides a lithium-rich manganese-based positive electrode active material. The lithium-rich manganese-based positive electrode material is a multi-layer coated structure. Under the joint action of the coating layer and the core, the storage capacity of the lithium-rich manganese-based positive electrode active material is significantly improved.

[0006] The present invention also provides a method for preparing a lithium-rich manganese-based positive electrode active material. The preparation method is simple to operate and can prepare the lithium-rich manganese-based positive electrode active material.

[0007] The present invention also provides a positive electrode sheet, which includes the above-mentioned lithium-rich manganese-based positive electrode active material and has excellent storage performance.

[0008] The present invention also provides a battery, which comprises the positive electrode sheet and thus has excellent performance.

[0009] In one aspect, the present invention provides a lithium-rich manganese-based positive electrode active material, comprising a lithium-rich manganese-based core, a first coating layer coated on at least a portion of the surface of the lithium-rich manganese-based core, and a second coating layer coated on at least a portion of the surface of the first coating layer;

[0010] Wherein, the chemical formula of the lithium-rich manganese-based core is Li 1+x Ni a Mn b M c O 2+x; Wherein, 0.25≤x≤0.4, a+b+c=1, 0.33≤a≤0.35, 0.63≤b≤0.65, 0≤c≤0.02; M is selected from at least one of W, Ta, Nb, Ti, Sb, Al, Mg, Zr, Sr, and Mo;

[0011] The first coating layer comprises an X-doped nano-layered lithium cobalt oxide layer, wherein X is selected from at least two of Al, La, Nb, Sr, Ti, Mn, Mo, Ta, W, K, B, and F;

[0012] The second coating layer includes a fast ion conductor and / or a spinel-like cobalt-lithium compound.

[0013] In the lithium-rich manganese-based positive electrode active material as described above, the fast ion conductor is selected from tungstate compounds or borate compounds.

[0014] As described above, the lithium-rich manganese-based positive electrode active material, the D50 particle size of the lithium-rich manganese-based core is 3 μm-7 μm.

[0015] The lithium-rich manganese-based positive electrode active material as described above, wherein the thickness of the first coating layer is 5nm-20nm;

[0016] And / or, the thickness of the second coating layer is 5nm-20nm.

[0017] Another aspect of the present invention provides a method for preparing the lithium-rich manganese-based positive electrode active material as described above, comprising the following steps:

[0018] 1) subjecting a mixture including nickel manganese hydroxide, M source and lithium hydroxide to a first sintering treatment to obtain a first precursor;

[0019] 2) subjecting the mixture including the first precursor, the X source, the cobalt source and the lithium source to a second sintering treatment at 700° C.-800° C. for 5-10 hours to obtain a second precursor;

[0020] 3) performing an acid wash treatment on the second precursor, and then performing a third sintering treatment to obtain a lithium-rich manganese-based positive electrode active material;

[0021] Wherein M is selected from at least one of W, Ta, Nb, Ti, Sb, Al, Mg, Zr, Sr, and Mo; and X is selected from at least two of Al, La, Nb, Sr, Ti, Mn, Mo, Ta, W, K, B, and F.

[0022] In the preparation method as described above, the pickling solution used in the pickling treatment is selected from tungstic acid solution or boric acid solution.

[0023] In the preparation method as described above, the mass concentration of the tungstic acid solution is 5%-10%;

[0024] And / or, the mass concentration of the boric acid solution is 5%-10%.

[0025] In the preparation method as described above, the temperature of the first sintering treatment is 900°C-1000°C, the time is 10-20h, and the heating rate is 3°C / min-5°C / min;

[0026] And / or, the heating rate of the second sintering treatment is 3°C / min-5°C / min;

[0027] And / or, the temperature of the third sintering treatment is 450° C.-600° C., and the time is 3-5 hours.

[0028] In another aspect, the present invention provides a positive electrode sheet, comprising the lithium-rich manganese-based positive electrode active material as described above or the lithium-rich manganese-based positive electrode active material prepared by the preparation method as described above.

[0029] Another aspect of the present invention provides a battery, comprising the positive electrode sheet as described above.

[0030] The lithium-rich manganese-based positive electrode active material provided by the present invention is composed of a core with a specific chemical formula and a first coating layer and a second coating layer with a specific composition. On the one hand, the higher lithium and manganese content in the core with a specific chemical formula helps to improve the thermal stability and safety of the positive electrode active material, and under the coating effect of the nano-layered lithium cobalt oxide doped with elements, the material structure can be stabilized by the doped elements, reducing the phase change and volume change that may occur during the charging and discharging process. On the other hand, the second coating layer including a fast ion conductor helps to improve the conductivity of lithium ions and reduce the interface impedance, thereby improving the rate performance and cycle performance of the material. By optimizing the core composition and the carefully designed coating layer structure, high capacity, high stability and excellent cycle performance are achieved, making it perform well in energy storage applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a TEM image of the lithium-rich manganese-based positive electrode active material provided in Example 1 of the present invention, magnified 200,000 times;

[0032] Figure 2 The lithium-rich manganese-based positive electrode active material provided in Example 1 of the present invention Figure 1 TEM-EDS line scan test curve;

[0033] Figure 3 This is a TEM image of the lithium-rich manganese-based positive electrode active material provided in Example 1 of the present invention, magnified 1 million times;

[0034] Figure 4 This is a local SAED test diagram of the lithium-rich manganese-based positive electrode active material provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Lithium-rich manganese-based materials are prone to structural changes during the charge and discharge process, such as the transformation of layered structures into spinel or rock salt phases, which causes the material structure to collapse and leads to capacity loss. In addition, lithium-rich manganese-based materials have poor compatibility with electrolytes, resulting in active interfacial reactions. Under the action of electrolytes, the manganese element in lithium-rich manganese-based materials dissolves and deposits, increasing interfacial impedance and affecting battery performance.

[0037] Therefore, if the structural degradation and interfacial side reactions of lithium-rich manganese-based materials during the cycle process can be suppressed, the storage capacity of lithium-rich manganese-based materials will be significantly improved.

[0038] In one aspect, the present invention provides a lithium-rich manganese-based positive electrode active material, comprising a lithium-rich manganese-based core, a first coating layer coated on at least a portion of the surface of the lithium-rich manganese-based core, and a second coating layer coated on at least a portion of the surface of the first coating layer;

[0039] Among them, the chemical formula of the lithium-rich manganese-based core is Li 1+x Ni a Mn b M c O 2+x ; Wherein, 0.25≤x≤0.4, a+b+c=1, 0.33≤a≤0.35, 0.63≤b≤0.65, 0≤c≤0.02; M is selected from at least one of W, Ta, Nb, Ti, Sb, Al, Mg, Zr, Sr, and Mo;

[0040] The first coating layer includes X-doped nano-layered lithium cobalt oxide, where X is selected from at least two of Al, La, Nb, Sr, Ti, Mn, Mo, Ta, W, K, B, and F;

[0041] The second coating layer includes a fast ion conductor and / or a spinel-like phase cobalt-lithium compound.

[0042] The lithium-rich manganese-based positive electrode active material provided by the present invention is a multi-layer coated core-shell structure, wherein the lithium-rich manganese-based compound serves as the core, and layered lithium cobalt oxide is coated on the surface of the core to form a first coating layer, and a second coating layer including a fast ion conductor is coated on the surface of the first coating layer.

[0043] The first coating layer includes X-doped nano-layered lithium cobalt oxide. In the layered lithium cobalt oxide structure, lithium ions and cobalt oxygen layers are arranged alternately, which is conducive to the insertion and extraction of lithium ions. Nano-layered lithium cobalt oxide means that the particle size of layered lithium cobalt oxide is at the nanometer level, which can further accelerate the diffusion of lithium ions, increase the reaction activity, and thus improve the rate performance of the battery.

[0044] When X is selected from at least two of the above elements, different doping elements can occupy different positions in the lattice, thereby enhancing the structural stability of the material, reducing the structural collapse caused by volume change during charging and discharging, and thus improving the structural stability of the positive electrode active material.

[0045] The fast ion conductor in the present invention refers to a lithium ion fast ion conductor, which has a high ionic conductivity and can enable rapid migration of lithium ions. In addition, the lithium ion fast ion conductor has good chemical stability in an electrochemical environment and excellent interface stability, and can significantly extend the cycle life of the battery.

[0046] It is understandable that there may be a certain transition region between the lithium-rich manganese-based core and the first coating layer, so that the interfaces can be more closely bonded, thereby improving the mechanical strength of the lithium-rich manganese-based positive electrode active material.

[0047] In a specific embodiment, the layered lithium cobalt oxide near the lithium-rich manganese-based core of the first coating layer is combined with part of the lithium-rich manganese-based core to form a surface doping effect, thereby enhancing the ability to resist the transformation of the layered phase to the spinel phase structure during material storage and enhancing the surface structure stability.

[0048] The lithium-rich manganese-based positive electrode active material provided by the present invention improves the energy density, cycle life and safety of lithium-ion batteries through a multilayer structure and element doping, and can enable the battery to have excellent cycle performance by optimizing the composition and structure of the core and coating layers.

[0049] The application of different types of fast ion conductors in batteries will affect the ion conduction efficiency, interface stability, cycle life, safety and overall energy density of the battery. In a specific embodiment, the fast ion conductor is selected from tungstate compounds or borate compounds.

[0050] In detail, tungstate chemicals include but are not limited to Li2WO4, Li2W2O7, Li4WO5, Li4CoWO6; borate compounds include but are not limited to Li3BO3, LiCoBO3.

[0051] Tungstate compounds or borate compounds have good chemical stability and are not prone to side reactions with electrolytes, thereby providing good protection for the inner core. At the same time, tungstate compounds or borate compounds, as fast ion conductors, have high ionic conductivity and can significantly improve the charge and discharge performance of the battery. The phase structure in the spinel-like cobalt-lithium compound has good structural stability and conductivity, which helps to improve the cycle stability and safety of the material. Under the synergistic effect of fast ion conductors and / or spinel-like cobalt-lithium compounds, further protection of the first coating layer and the inner core can be achieved while further improving the storage performance of the battery.

[0052] The D50 particle size indicates that 50% of the particles in the material have a diameter less than or equal to this value, that is, D50 is the median of the particle size, which means that half of the particles are smaller than this size and the other half are larger than this size. As a positive electrode active material, the D50 particle size of the lithium-rich manganese-based core has an important influence on the electrochemical properties and cycle stability of the positive electrode active material.

[0053] In one specific embodiment, the D50 particle size of the lithium-rich manganese-based core is 3 μm-7 μm.

[0054] The D50 particle size of the lithium-rich manganese-based core can be measured using common testing methods in the art, such as laser diffraction, screening, microscope image analysis, etc.

[0055] In detail, the D50 particle size of the lithium-rich manganese-based core includes but is not limited to 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm or a range between any two of them.

[0056] When the D50 particle size of the lithium-rich manganese-based core is within the above range, the diffusion path of lithium ions can be shortened, the charge and discharge efficiency can be improved, and a balance between reaction activity and structural stability can be achieved.

[0057] As a core-shell structure, the thickness of each coating layer not only affects the structural stability, but also has a certain impact on the electrochemical performance of the positive electrode active material.

[0058] The thickness of each coating layer can be detected by using a transmission electron microscope, an atomic force microscope or other commonly used detection means in the art.

[0059] In a specific embodiment, the thickness of the first coating layer is 5nm-20nm; in detail, the thickness of the first coating layer includes but is not limited to 5nm, 6nm, 8nm, 10nm, 12nm, 14nm, 16nm, 18nm, 20nm or a range between any two thereof.

[0060] When the thickness of the first coating layer is within the above range, the moderate thickness can effectively cover the surface of the positive electrode material, reduce the oxygen activity on the positive electrode surface, and accelerate the electron conduction rate without affecting the lithium ion transmission.

[0061] In another specific embodiment, the thickness of the second coating layer is 5nm-20nm. Specifically, the thickness of the second coating layer includes but is not limited to 5nm, 6nm, 8nm, 10nm, 12nm, 14nm, 16nm, 18nm, 20nm or a range between any two thereof.

[0062] When the thickness of the second coating layer is within the above range, the surface activity of the first coating layer can be effectively passivated, the coating layer's ability to resist electrolyte corrosion can be modified, and lithium ion transport can be further improved.

[0063] Another aspect of the present invention provides a method for preparing the lithium-rich manganese-based positive electrode active material as described above, comprising the following steps:

[0064] 1) subjecting a mixture including nickel manganese hydroxide, M source and lithium hydroxide to a first sintering treatment to obtain a first precursor;

[0065] 2) subjecting the mixture including the first precursor, the X source, the cobalt source and the lithium source to a second sintering treatment at 700° C.-800° C. for 5-10 hours to obtain a second precursor;

[0066] 3) performing an acid wash treatment on the second precursor, and then performing a third sintering treatment to obtain a lithium-rich manganese-based positive electrode active material;

[0067] Wherein M is selected from at least one of W, Ta, Nb, Ti, Sb, Al, Mg, Zr, Sr, and Mo; and X is selected from at least two of Al, La, Nb, Sr, Ti, Mn, Mo, Ta, W, K, B, and F.

[0068] The preparation method provided by the present invention can prepare the above-mentioned lithium-rich manganese-based positive electrode active material.

[0069] Specifically, in step 1), nickel manganese hydroxide, M source, and lithium hydroxide are weighed and uniformly mixed according to a certain molar relationship, and the mixture is subjected to a first sintering treatment to obtain a chemical formula satisfying Li 1+x Ni a Mn b M c O 2+x a first precursor; wherein, 0.25≤x≤0.4, a+b+c=1, 0.33≤a≤0.35, 0.63≤b≤0.65, 0≤c≤0.02.

[0070] The present invention does not limit the specific type of M source, and a common type in the art may be selected. For example, when M is Zr, the M source may be Zr(OH)4, ZrO2, etc.; when M is Al, the M source may be AlOOH, Al(OH)3, Al2O3.

[0071] In step 2), the mixture obtained by uniformly mixing the first precursor, X source, cobalt source and lithium source is subjected to a second sintering treatment at 700°C-800°C for 5-10h to obtain a second precursor coated with the first precursor, wherein the outer layer of the second precursor is X-doped nano-layered lithium cobalt oxide.

[0072] The present invention does not limit the specific types of the cobalt source, lithium source, and X source. For example, the cobalt source can be CoOOH, Co3O4, Co2O3, or CoO; the lithium source can be lithium hydroxide, Li2CO3, or LiO. When X is Al, alumina can be used; and when X is La, La2O3 can be used.

[0073] The relatively high temperature is conducive to the combination of some X-doped nano-layered lithium cobalt oxide with the first precursor to form a surface doping effect, while the remaining X-doped nano-layered lithium cobalt oxide far away from the first precursor can give play to the high crystallinity and surface stability brought by multi-element doping, which is used to reduce the side reaction between the material body and the electrolyte during storage, and at the same time give play to the advantage of high electronic conductivity of lithium cobalt oxide to reduce the initial impedance of the material and the speed of impedance increase.

[0074] In step 3), the second precursor is pickled with an acid solution, and then subjected to a third sintering treatment to obtain a lithium-rich manganese-based positive electrode active material;

[0075] On the one hand, the pickling treatment can remove impurities and unreacted by-products remaining on the surface of the second precursor and reduce the residual alkali on the surface. On the other hand, the pickling treatment can cause the pickling solution to react with the surface of the second precursor to undergo an acid-base delithiation reaction to form a lithium-poor spinel-like cobalt-lithium compound, laying the foundation for the subsequent third sintering treatment to obtain a lithium-rich manganese-based positive electrode active material coated with a second coating layer.

[0076] Subsequently, under the action of the third sintering treatment, the structural defects that may be introduced by the pickling treatment are repaired, and the crystallinity and structural stability of the material are improved.

[0077] The preparation method provided by the invention is simple to operate, and the prepared lithium-rich manganese-based positive electrode active material has excellent storage performance.

[0078] The selection of pickling solution in the pickling treatment will directly affect the type of fast ion conductor in the second coating layer. In a specific embodiment, the pickling solution used in the pickling treatment is selected from a tungstic acid solution or a boric acid solution.

[0079] When the pickling solution is selected from a tungstic acid solution or a boric acid solution, the fast ion conductor in the second coating layer is a tungstate compound or a borate compound, which has a positive effect on the storage performance of the lithium-rich manganese-based positive electrode active material.

[0080] In a specific embodiment, the mass concentration of the tungstic acid solution is 5%-10%; in detail, the mass concentration of the tungstic acid solution includes but is not limited to 5%, 6%, 7%, 8%, 9%, 10% or a range between any two thereof.

[0081] In another specific embodiment, the mass concentration of the boric acid solution is 5%-10%.

[0082] When the mass concentration of tungstic acid solution or boric acid solution is within the above range, it not only fully reacts with the residual alkali on the surface, but also reacts with the first coating layer to form a spinel-phase lithium cobalt compound, passivate its interfacial activity, increase the difficulty of side reactions and further improve lithium ion transmission.

[0083] Further, in a specific embodiment, the temperature of the first sintering treatment is 900° C.-1000° C., the time is 10-20 hours, and the heating rate is 3° C. / min-5° C. / min.

[0084] When the first sintering treatment meets the above parameters, it can promote the formation of a crystal structure in the lithium-rich manganese-based core, reduce lattice defects in the material, achieve moderate growth of the core, and form an ideal particle distribution size, which has a positive impact on the conductivity and ion transport properties of the electrode material.

[0085] The heating rate of the second sintering treatment is 3℃ / min-5℃ / min; a moderate heating rate helps to control the microstructure of the material and avoid excessive growth or uneven particles caused by too fast heating. A more moderate heating rate can reduce the thermal stress inside the material and reduce the risk of cracks or other defects during the sintering process.

[0086] The temperature of the third sintering treatment is 450°C-600°C, and the time is 3-5h.

[0087] The precise control of the temperature and time of the third sintering treatment is to achieve an efficient and economical production process while ensuring material performance. This step ensures that the final positive electrode active material has excellent electrochemical properties and structural stability, suitable for high-performance lithium-ion battery applications.

[0088] In another aspect, the present invention provides a positive electrode sheet, comprising the lithium-rich manganese-based positive electrode active material as described above or the lithium-rich manganese-based positive electrode active material prepared by the preparation method as described above.

[0089] The positive electrode sheet of the present invention specifically comprises a positive electrode current collector and a positive electrode active layer formed of a lithium-rich manganese-based positive electrode active material and arranged on the surface of the positive electrode current collector.

[0090] When preparing the positive electrode sheet, for example, the lithium-rich manganese-based positive electrode active material of the present invention, the conductive agent and the binder can be dispersed in an appropriate amount of N-methylpyrrolidone (NMP) solvent, and the mixture is stirred and mixed to form a uniform positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector, and the positive electrode sheet is obtained after drying, rolling and cutting. In a specific embodiment, the positive electrode active layer includes 70wt%-99wt% of lithium-rich manganese-based positive electrode active material, 0.5wt%-15wt% of conductive agent, and 0.5wt%-15wt% of binder according to the mass percentage, and further includes 80wt%-98wt% of lithium-rich manganese-based positive electrode active material, 1wt%-10wt% of conductive agent, and 1wt%-10wt% of binder.

[0091] Among them, the material of the positive electrode current collector can be at least one of aluminum foil and nickel foil; the conductive agent can be selected from at least one of carbon black, acetylene black, graphene, Ketjen black, and carbon fiber; the binder can be selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, and polyurethane.

[0092] Since the lithium-rich manganese-based positive electrode active material provided by the present invention has excellent storage performance, the positive electrode sheet provided by the present invention also has excellent storage performance.

[0093] Another aspect of the present invention provides a battery, comprising the positive electrode sheet as described above.

[0094] It is conceivable that the battery provided by the present invention includes, in addition to the above-mentioned positive electrode sheet, a negative electrode sheet, an electrolyte and a separator.

[0095] The present invention does not strictly limit the negative electrode active material in the negative electrode sheet, and can be at least one of the negative electrode active materials commonly used in lithium-ion batteries, such as graphite, hard carbon, soft carbon, mesophase carbon microbeads, silicon-based negative electrode materials (mainly including silicon oxide, silicon-carbon negative electrode), tin-based negative electrode materials (mainly including tin, tin alloy), etc.

[0096] The present invention does not strictly limit the selection of the electrolyte, and may include one or more of the solvents commonly used in lithium-ion battery electrolytes, and electrolyte lithium salts commonly used in lithium-ion electrolytes, for example: the solvent may be ethylene carbonate, propylene carbonate, butylene carbonate, fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), diethyl carbonate (DEC), difluoroethylene carbonate (DFEC), dipropyl carbonate, ethyl methyl carbonate (EMC), ethyl acetate, ethyl propionate, propyl acetate, propyl propionate, sulfolane, γ-butyrolactone, etc.; the lithium salt may be, for example, one or more of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI).

[0097] The present invention does not strictly limit the material selection of the diaphragm, which can be a diaphragm material commonly used in lithium-ion batteries, such as a polypropylene diaphragm (PP), a polyethylene diaphragm (PE), a polypropylene / polyethylene double-layer composite film (PP / PE), a polyimide electrospinning diaphragm (PI), a polypropylene / polyethylene / polypropylene three-layer composite film (PP / PE / PP), a cellulose non-woven fabric diaphragm, or a diaphragm with a ceramic coating.

[0098] When preparing lithium-ion batteries, the positive electrode sheet, separator and negative electrode sheet are wound or stacked to obtain a bare cell, and the bare cell is packaged in a pre-stamped aluminum-plastic film bag. After the packaged battery is dried at 85°C, the electrolyte is injected into the dry battery, and the battery is placed, formed and sealed for the second time to complete the preparation of the lithium-ion battery.

[0099] The preparation method of the lithium-rich manganese-based positive electrode active material provided by the present invention will be described in detail below with reference to specific embodiments.

[0100] Example 1

[0101] The chemical formula of the lithium-rich manganese-based core in the lithium-rich manganese-based positive electrode active material provided in this embodiment is Li 1.31 Ni 0.34 Mn 0.65 Al 0.005 Zr 0.005 O 2.31 , the preparation method comprises the following steps:

[0102] 1. Based on the stoichiometric ratio in the above formula, nickel manganese hydroxide, Zr(OH)4, AlOOH and an excess of 5% lithium hydroxide (i.e., the molar content is (1.31+0.05=1.36) compared to other components) are mixed until uniform to obtain a mixture, and the mixture is subjected to a first sintering treatment: the average heating rate of the first sintering treatment is 5°C / min, and the temperature is kept when the temperature reaches the first sintering temperature of 850°C. After the holding time reaches 12 hours, the temperature is lowered to room temperature to obtain a mixture with the chemical formula of Li 1.31 Ni 0.34 Mn 0.65 Al 0.005 Zr 0.005 O 2.31 The first precursor.

[0103] 2. The first precursor is subjected to a second sintering treatment with 5000ppm Co(OH)2, 500ppm Al2O3, 100ppm La2O3, and 500ppm LiOH based on the mass of the positive electrode material: the average heating rate of the second sintering treatment is 3°C / min. When the temperature reaches the second sintering temperature of 750°C, it is kept for 8h and then cooled to room temperature to obtain a second precursor coated with Al and La co-doped nano-layered lithium cobalt oxide.

[0104] 3. The second precursor is immersed and dried in tungstic acid with a mass concentration of 10%, and then subjected to a third sintering treatment. The average heating rate of the third sintering treatment is 5°C / min. When the temperature reaches the third sintering temperature of 450°C, it is kept for 4 hours and then cooled to obtain a lithium-rich manganese-based positive electrode active material coated with a second coating layer.

[0105] The lithium-rich manganese-based positive electrode active material provided in this embodiment was subjected to TEM and EDS tests, wherein Figure 1 This is the TEM test picture. Figure 2 is the EDS test curve, according to Figure 1 and Figure 2 It can be seen that the element contents of the first and second coating layers at the surface and the bulk positive electrode material vary significantly, indicating that a reaction occurred between the coating layers to form a composite structure; Figure 3 This is an enlarged TEM test image, where: Figure 3 1 in the figure is the second coating layer, Figure 3 2 in it is a lithium-rich manganese-based core. Figure 3 3 in the figure is the first coating layer, Figure 4 It is the SAED test diagram, according to Figure 3 and Figure 4 It can be seen that the nano-layered lithium cobalt oxide as the first coating layer undergoes lattice growth on the surface of the lithium-rich manganese-based core, while the surface of the second coating layer forms a fast ion conductor coating layer and a spinel-like cobalt-lithium compound due to the reaction of tungstic acid with lithium cobalt oxide and residual lithium on the surface.

[0106] Example 2

[0107] The chemical formula of the lithium-rich manganese-based core in the lithium-rich manganese-based positive electrode active material provided in this embodiment is Li 1.31 Ni 0.34 Mn 0.65 Al 0.005 Zr 0.005 O 2.31 , the preparation method comprises the following steps:

[0108] 1. Based on the stoichiometric ratio in the above formula, nickel manganese hydroxide, Zr(OH)4, AlOOH and an excess of 5% lithium hydroxide (i.e., the molar content is (1.31+0.05=1.36) compared to other components) are mixed until uniform to obtain a mixture, and the mixture is subjected to a first sintering treatment: the average heating rate of the first sintering treatment is 5°C / min, and the temperature is kept when the temperature reaches the first sintering temperature of 850°C. After the holding time reaches 12 hours, the temperature is lowered to room temperature to obtain a mixture with the chemical formula Li 1.31 Ni 0.34 Mn 0.65 Al 0.005 Zr 0.00 5O 2.31 The first precursor.

[0109] 2. The first precursor is subjected to a second sintering treatment with 2500ppm Co(OH)2, 250ppm Al2O3, 50ppm La2O3, and 250ppm LiOH based on the mass of the positive electrode material: the average heating rate of the second sintering treatment is 3°C / min. When the temperature reaches the second sintering temperature of 750°C, it is kept for 8 hours and then cooled to room temperature to obtain a second precursor coated with Al and La co-doped nano-layered lithium cobalt oxide.

[0110] 3. The second precursor is immersed and dried in tungstic acid with a mass concentration of 10%, and then subjected to a third sintering treatment. The average heating rate of the third sintering treatment is 5°C / min. When the temperature reaches the third sintering temperature of 450°C, it is kept for 4 hours and then cooled to obtain a lithium-rich manganese-based positive electrode active material coated with a second coating layer.

[0111] Example 3

[0112] The chemical formula of the lithium-rich manganese-based core in the lithium-rich manganese-based positive electrode active material provided in this embodiment is Li 1.31 Ni 0.34 Mn 0.65 Al 0.005 Zr 0.005 O 2.31 , the preparation method comprises the following steps:

[0113] 1. Based on the stoichiometric ratio in the above formula, nickel manganese hydroxide, Zr(OH)4, AlOOH and an excess of 5% lithium hydroxide (i.e., the molar content is (1.31+0.05=1.36) compared to other components) are mixed until uniform to obtain a mixture, and the mixture is subjected to a first sintering treatment: the average heating rate of the first sintering treatment is 5°C / min, and the temperature is kept when the temperature reaches the first sintering temperature of 850°C. After the holding time reaches 12 hours, the temperature is lowered to room temperature to obtain a mixture with the chemical formula Li 1.31 Ni 0.34 Mn 0.65 Al 0.005 Zr 0.00 5O 2.31 The first precursor.

[0114] 2. The first precursor is subjected to a second sintering treatment with 10000ppm Co(OH)2, 1000ppm Al2O3, 200ppm La2O3, and 1000ppm LiOH based on the mass of the positive electrode material: the average heating rate of the second sintering treatment is 3°C / min. When the temperature reaches the second sintering temperature of 750°C, it is kept for 8h and then cooled to room temperature to obtain a second precursor coated with Al and La co-doped nano-layered lithium cobalt oxide.

[0115] 3. The second precursor is immersed and dried in boric acid with a mass concentration of 10%, and then subjected to a third sintering treatment. The average heating rate of the third sintering treatment is 5°C / min. When the temperature reaches the third sintering temperature of 350°C, it is kept for 4 hours and then cooled to obtain a lithium-rich manganese-based positive electrode active material coated with a second coating layer.

[0116] Example 4

[0117] The chemical formula of the lithium-rich manganese-based core in the lithium-rich manganese-based positive electrode active material provided in this embodiment is Li 1.31 Ni 0.34 Mn 0.65 Al 0.005 Zr 0.005 O 2.31 , the preparation method comprises the following steps:

[0118] 1. Based on the stoichiometric ratio in the above formula, nickel manganese hydroxide, Zr(OH)4, AlOOH and an excess of 5% lithium hydroxide (i.e., the molar content is (1.31+0.05=1.36) compared to other components) are mixed until uniform to obtain a mixture, and the mixture is subjected to a first sintering treatment: the average heating rate of the first sintering treatment is 5°C / min, and the temperature is kept when the temperature reaches the first sintering temperature of 850°C. After the holding time reaches 12 hours, the temperature is lowered to room temperature to obtain a mixture with the chemical formula Li 1.31 Ni 0.34 Mn 0.65 Al0.005 Zr 0.00 5O 2.31 The first precursor.

[0119] 2. The first precursor is subjected to a second sintering treatment with 5000ppm Co(OH)2, 500ppm Al2O3, 100ppm SrO, and 500ppm LiOH based on the mass of the positive electrode material: the average heating rate of the second sintering treatment is 3°C / min. When the temperature reaches the second sintering temperature of 750°C, it is kept for 8h and then cooled to room temperature to obtain a second precursor coated with Al and Sr co-doped nano-layered lithium cobalt oxide.

[0120] 2. The second precursor is immersed and dried in boric acid with a mass concentration of 10%, and then subjected to a third sintering treatment. The average heating rate of the third sintering treatment is 5°C / min. When the temperature reaches the third sintering temperature of 350°C, it is kept for 4 hours and then cooled to obtain a lithium-rich manganese-based positive electrode active material coated with a second coating layer.

[0121] Example 5

[0122] The chemical formula of the lithium-rich manganese-based core in the lithium-rich manganese-based positive electrode active material provided in this embodiment is Li 1.31 Ni 0.34 Mn 0.65 Al 0.005 Zr 0.005 O 2.31 , the preparation method comprises the following steps:

[0123] 1. Based on the stoichiometric ratio in the above formula, nickel manganese hydroxide, Zr(OH)4, AlOOH and an excess of 5% lithium hydroxide (i.e., the molar content is (1.31+0.05=1.36) compared to other components) are mixed until uniform to obtain a mixture, and the mixture is subjected to a first sintering treatment: the average heating rate of the first sintering treatment is 5°C / min, and the temperature is kept when the temperature reaches the first sintering temperature of 850°C. After the holding time reaches 12 hours, the temperature is lowered to room temperature to obtain a mixture with the chemical formula Li 1.31 Ni 0.34 Mn 0.65 Al 0.005 Zr 0.00 5O 2.31 The first precursor.

[0124] 2. The first precursor is subjected to a second sintering treatment with 10000ppm Co(OH)2, 1000ppm Al2O3, 200ppm SrO, and 1000ppm LiOH based on the mass of the positive electrode material: the average heating rate of the second sintering treatment is 3°C / min. When the temperature reaches the second sintering temperature of 750°C, it is kept for 8h and then cooled to room temperature to obtain a second precursor coated with Al and Sr co-doped nano-layered lithium cobalt oxide.

[0125] 3. The second precursor is immersed and dried in boric acid with a mass concentration of 10%, and then subjected to a third sintering treatment. The average heating rate of the third sintering treatment is 5°C / min. When the temperature reaches the third sintering temperature of 350°C, it is kept for 4 hours and then cooled to obtain a lithium-rich manganese-based positive electrode active material coated with a second coating layer.

[0126] Example 6

[0127] The preparation method of the lithium-rich manganese-based positive electrode active material provided in this embodiment is basically the same as that in Example 1, except that:

[0128] In step 3), tungstic acid is replaced by phosphoric acid.

[0129] Example 7

[0130] The preparation method of the lithium-rich manganese-based positive electrode active material provided in this embodiment is basically the same as that in Example 1, except that:

[0131] In step 3), the mass concentration of the tungstic acid solution is 2%.

[0132] Example 8

[0133] The preparation method of the lithium-rich manganese-based positive electrode active material provided in this embodiment is basically the same as that in Example 1, except that:

[0134] In step 3), the temperature of the third sintering treatment is 300° C. and the time is 5 hours.

[0135] Example 9

[0136] The chemical formula of the lithium-rich manganese-based core in the lithium-rich manganese-based positive electrode active material provided in this embodiment is Li 1.35 Ni 0.34 Mn 0.65 Mg 0.005 Sr 0.005 O 2.35 , the preparation method comprises the following steps:

[0137] 1. Based on the stoichiometric ratio in the above formula, nickel manganese hydroxide, Mg(OH)2, Sr(OH)2 and an excess of 5% lithium hydroxide (i.e., the molar content is (1.35+0.05=1.4) compared to other components) are mixed until uniform to obtain a mixture, and the mixture is subjected to a first sintering treatment: the average heating rate of the first sintering treatment is 5°C / min, and the temperature is kept when the temperature reaches the first sintering temperature of 850°C. After the holding time reaches 12 hours, the temperature is lowered to room temperature to obtain a mixture with the chemical formula Li 1.35 Ni 0.34 Mn 0.65 Mg 0.005 Sr 0.00 5O 2.35 The first precursor.

[0138] 2. The first precursor is subjected to a second sintering treatment with 5000ppm Co(OH)2, 500ppm Al2O3, 100ppm TiO2, and 500ppm LiOH based on the mass of the positive electrode material: the average heating rate of the second sintering treatment is 3°C / min. When the temperature reaches the second sintering temperature of 750°C, it is kept for 8h and then cooled to room temperature to obtain a second precursor coated with Al and Ti co-doped nano-layered lithium cobalt oxide.

[0139] 2. The second precursor is immersed and dried in boric acid with a mass concentration of 10%, and then subjected to a third sintering treatment. The average heating rate of the third sintering treatment is 5°C / min. When the temperature reaches the third sintering temperature of 350°C, it is kept for 4 hours and then cooled to obtain a lithium-rich manganese-based positive electrode active material coated with a second coating layer.

[0140] Example 10

[0141] The chemical formula of the lithium-rich manganese-based core in the lithium-rich manganese-based positive electrode active material provided in this embodiment is Li 1.33 Ni 0.35 Mn 0.64 W 0.005 Zr 0.005 O 2.33 , the preparation method comprises the following steps:

[0142] 1. Based on the stoichiometric ratio in the above formula, nickel manganese hydroxide, WO3, Zr(OH)4 and an excess of 5% lithium hydroxide (i.e., the molar content is (1.33+0.05=1.38) compared to other components) are mixed until uniform to obtain a mixture, and the mixture is subjected to a first sintering treatment: the average heating rate of the first sintering treatment is 5°C / min, and the temperature is kept when the temperature reaches the first sintering temperature of 850°C. After the holding time reaches 12 hours, the temperature is lowered to room temperature to obtain a chemical formula of Li 1.33 Ni 0.35 Mn 0.64 W 0.005Zr 0.005 O 2.33 The first precursor.

[0143] 2. The first precursor is subjected to a second sintering treatment with 5000ppm Co(OH)2, 500ppm Mn2O3, 100ppm B2O3, and 500ppm LiOH based on the mass of the positive electrode material: the average heating rate of the second sintering treatment is 3°C / min. When the temperature reaches the second sintering temperature of 750°C, it is kept for 8h and then cooled to room temperature to obtain a second precursor coated with Mn and B co-doped nano-layered lithium cobalt oxide.

[0144] 2. The second precursor is immersed and dried in boric acid with a mass concentration of 10%, and then subjected to a third sintering treatment. The average heating rate of the third sintering treatment is 5°C / min. When the temperature reaches the third sintering temperature of 350°C, it is kept for 4 hours and then cooled to obtain a lithium-rich manganese-based positive electrode active material coated with a second coating layer.

[0145] Comparative Example 1

[0146] The preparation method of the positive electrode active material provided in this comparative example is basically the same as that in Example 1, except that:

[0147] The second sintering process was not performed.

[0148] Comparative Example 2

[0149] The preparation method of the positive electrode active material provided in this comparative example is basically the same as that in Example 1, except that:

[0150] No pickling treatment and no third sintering treatment were performed.

[0151] Comparative Example 3

[0152] The preparation method of the positive electrode active material provided in this comparative example is basically the same as that in Example 3, except that:

[0153] No pickling treatment and no third sintering treatment were performed.

[0154] Comparative Example 4

[0155] The preparation method of the lithium-rich manganese-based positive electrode active material provided in this comparative example is basically the same as that in Example 1, except that:

[0156] In step 1), the heating rate of the second sintering treatment is 10° C. / min, the temperature of the second sintering treatment is 685° C., and the time is 5 hours.

[0157] Test Case

[0158] 1. Physical property test

[0159] The lithium-rich manganese-based positive electrode active materials provided in all embodiments are tested, including the following steps:

[0160] 2) D50 particle size test of lithium-rich manganese-based core: The particle size can be tested by a laser particle size analyzer. Optionally, the laser particle size analyzer can be a Malvern Panalytical Mastersizer 2000 laser particle size analyzer.

[0161] 3) Thickness test of the first coating layer and the second coating layer: The thickness test can be performed by a transmission electron microscope. Optionally, the transmission electron microscope can be a Thermo Fisher Talos 200X.

[0162] The specific test results are shown in Table 1.

[0163] Table 1

[0164]

[0165]

[0166] 2. Electrochemical performance test

[0167] 1) Capacity test

[0168] The positive electrode active materials, conductive agents and binders provided in all the embodiments and comparative examples were mixed in turn (94:3:3) to obtain positive electrode active slurry, which was made into pole pieces. PE separators, lithium metal, electrolyte (including LiPF6, EC, EMC, DEC and FEC, the content of LiPF6 in the electrolyte is 1M, the volume ratio of EC, EMC and DEC is 1:1:1, and the mass percentage of FEC in the electrolyte is 2%) were used to prepare CR2430 button batteries, and the capacity was tested at a current density of 0.2C in the voltage range of 2.5-4.55V. The specific test results are shown in Table 2.

[0169] 2) Storage performance test

[0170] The positive electrode active materials, conductive agents and binders provided in all the embodiments and comparative examples are sequentially mixed (94:3:3) to obtain a positive electrode active slurry, which is made into a pole sheet, and assembled with a negative pole sheet to obtain an electrode assembly, the electrode assembly is placed in an outer package, and an electrolyte is injected into the outer package to obtain a battery;

[0171] The negative electrode sheet includes a copper foil and a negative electrode active layer disposed on two surfaces of the copper foil, wherein the negative electrode active layer includes graphite, CMC, SP and SBR, and wherein the mass ratio of graphite, CMC, SP and SBR in the negative electrode active layer is 95.5:1.5:1:2;

[0172] The electrolyte includes LiPF6, EC, EMC, DEC and FEC. The content of LiPF6 in the electrolyte is 1M. The volume ratio of EC, EMC and DEC is 1:1:1. The mass percentage of FEC in the electrolyte is 2%.

[0173] The prepared battery was subjected to formation and capacity division, and then a capacity test was performed using a 0.33C current. The initial capacity was recorded and the battery was charged to 4.55V. The battery was placed in a 60°C oven and stored for 42 days. After storage, a 0.33C capacity test was performed again, and the capacity after 42 days was recorded. The capacity loss rate = 1-capacity after 42 days / initial capacity. The relevant data are shown in Table 2.

[0174] 3) Residual alkali test: Use a 1 / 10,000 electronic balance to weigh the positive electrode sample in a disposable plastic cup and record the sample mass; use a 1 / 10,000 balance to weigh 95.00 pure water and record the mass of the pure water. Add a magnet and seal it with plastic wrap or sealing film. Place the plastic cup on a magnetic stirrer at a speed of 700r / min and stir for 5 minutes. Use a vacuum pump to filter and pour all the filtrate into a clean plastic cup. Cover it with plastic wrap or sealing film for later use. Use an automatic potentiometric titrator to titrate with a standard solution of 0.1mol / L hydrochloric acid. See Table 2 for relevant test data.

[0175] Table 2

[0176]

[0177] It can be seen from Table 2 that compared with bulk doping, the lithium-rich manganese-based positive electrode active material provided by the present invention has a more obvious improvement effect on storage performance through surface coating. It can be seen from Examples 6-8 that the use of phosphoric acid as the pickling solution, lower pickling concentration and three sintering temperatures all have certain adverse effects on capacity, first efficiency and storage performance. From the positive electrode active materials provided in Comparative Examples 1-5, it can be seen that the lithium-rich manganese-based positive electrode active material provided by the present invention has a fast ion conductor and / or a spinel-like lithium cobalt compound formed on the surface, and the importance of interface protection of the first coating layer, otherwise it will lead to more serious electrochemical side reactions during the electrical performance test, thereby deteriorating battery performance.

[0178] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A lithium-rich manganese-based positive electrode active material, characterized in that: It comprises a lithium-rich manganese-based core, a first coating layer coated on at least a portion of the surface of the lithium-rich manganese-based core, and a second coating layer coated on at least a portion of the surface of the first coating layer; Wherein, the chemical formula of the lithium-rich manganese-based core is Li 1+x Ni a Mn b M c O 2+x ; Wherein, 0.25≤x≤0.4, a+b+c=1, 0.33≤a≤0.35, 0.63≤b≤0.65, 0≤c≤0.02; M is selected from at least one of W, Ta, Nb, Ti, Sb, Al, Mg, Zr, Sr, and Mo; The first coating layer comprises an X-doped nano-layered lithium cobalt oxide layer, wherein X is selected from at least two of Al, La, Nb, Sr, Ti, Mn, Mo, Ta, W, K, B, and F; The second coating layer includes a fast ion conductor and / or a spinel-like cobalt-lithium compound.

2. The lithium-rich manganese-based positive electrode active material according to claim 1, characterized in that: The fast ion conductor is selected from tungstate compounds or borate compounds.

3. The lithium-rich manganese-based positive electrode active material according to claim 1 or 2, characterized in that: The D50 particle size of the lithium-rich manganese-based core is 3 μm-7 μm.

4. The lithium-rich manganese-based positive electrode active material according to any one of claims 1 to 3, characterized in that: The thickness of the first coating layer is 5nm-20nm; And / or, the thickness of the second coating layer is 5nm-20nm.

5. A method for preparing the lithium-rich manganese-based positive electrode active material according to any one of claims 1 to 4, characterized in that: The following steps are involved: 1) subjecting a mixture including nickel manganese hydroxide, M source and lithium hydroxide to a first sintering treatment to obtain a first precursor; 2) subjecting a mixture including the first precursor, the X source, the cobalt source, and the lithium source to a second sintering treatment at 700° C. to 800° C. for 5 h to 10 h to obtain a second precursor; 3) performing an acid wash treatment on the second precursor, and then performing a third sintering treatment to obtain a lithium-rich manganese-based positive electrode active material; Wherein M is selected from at least one of W, Ta, Nb, Ti, Sb, Al, Mg, Zr, Sr, and Mo; and X is selected from at least two of Al, La, Nb, Sr, Ti, Mn, Mo, Ta, W, K, B, and F.

6. The preparation method according to claim 5, characterized in that: The pickling solution used in the pickling treatment is selected from tungstic acid solution or boric acid solution.

7. The preparation method according to claim 6, characterized in that: The mass concentration of the tungstic acid solution is 5%-10%; And / or, the mass concentration of the boric acid solution is 5%-10%.

8. The preparation method according to any one of claims 5 to 7, characterized in that: The temperature of the first sintering treatment is 900°C-1000°C, the time is 10-20h, and the heating rate is 3°C / min-5°C / min; And / or, the heating rate of the second sintering treatment is 3°C / min-5°C / min; And / or, the temperature of the third sintering treatment is 450° C.-600° C., and the time is 3-5 hours.

9. A positive electrode sheet, characterized in that: The invention comprises the lithium-rich manganese-based positive electrode active material as described in any one of claims 1 to 4 or the lithium-rich manganese-based positive electrode active material prepared by the preparation method as described in any one of claims 5 to 8.

10. A battery, characterized in that: Including the positive electrode sheet as described in claim 9.

Citation Information

Patent Citations

  • Positive electrode material and preparation method thereof, secondary battery and electric device

    CN116632190A

Cited By

  • Lithium-rich manganese-based positive electrode material and preparation method and application thereof

    CN121054668A

  • Lithium-rich manganese-based positive electrode active material and preparation method and application thereof

    CN121484043A

  • Positive electrode active material and preparation method and application thereof

    CN121617932A

  • Positive electrode active material, method for producing the same, and use thereof

    CN121617932B

  • Positive electrode active material and preparation method and application thereof

    CN121617946A